The Effectiveness of Lavender Aromatherapy on Blood Pressure among Elderly with Essential Hypertension - Dwi Yunita Rahmadhani (Palembang MediRose Publisher, 2022)
Background: Hypertension is a condition in which the systolic blood pressure is more than 120 mmHg, and the diastolic pressure is more than 80 mmHg. Lavender aromatherapy is a way to cure sickness which uses essential oil. Purpose: The purpose of this study is to analyse the effect of lavender aromatherapy on the changes in blood pressure in the Elderly with essential hypertension Methods: This study used a pra-experiment pretest and posttest design where the measurement of blood pressure is done twice before the lavender aromatherapy is given (pretest) and after the lavender aromatherapy is given (posttest). The population of this study is the patients with essential hypertension in the work area of one of the Public Health Centers in Jambi, Indonesia in 2018 which is 627 patients. Meanwhile, the sample used in this study is Purposive Sampling. The method used in this study is univariate and bivariate data analysis using T-Test. Results: Statistical test result shows that there was a significant effect of giving lavender aromatherapy on changes in blood pressure of patients with essential hypertension with p < 0.05; systole (p = 0.001) and diastole (p < 0.001). Conclusions: The use of alternative lavender aromatherapy as a therapy used to lower blood pressure in patients with essential hypertension. It is suggested to researchers who are interested to examine this topic of the effect of lavender aromatherapy on blood pressure in patients with essential hypertension to do further research in the same scope with a different variable.